Sociology : themes and perspectives - Haralambos, Michael; Holborn, Martin (London : Collins, 2008)
The seventh edition of this introduction to sociology includes a new chapter on Age and the Life Course as well as extensive updates of existing chapters. It offers thorough coverage of the latest A level specifications.
Previous ed.: 2004.
Includes bibliographical references (p. 900-927) and index.
Keywords: Sociology; Society